Clinical accuracy of instrument-based SARS-CoV-2 antigen diagnostic tests: a systematic review and meta-analysis - Manten, Katharina; Katzenschlager, Stephan; Brümmer, Lukas E.; Schmitz, Stephani; Gaeddert, Mary; Erdmann, Christian; Grilli, Maurizio; Pollock, Nira R.; Macé, Aurélien; Erkosar, Berra; Carmona, Sergio; Ongarello, Stefano; et al. (Virology journal, 2024)
During the COVID-19 pandemic, antigen diagnostic tests were frequently used for screening, triage, and diagnosis. Novel instrument-based antigen tests (iAg tests) hold the promise of outperforming their instrument-free, visually-read counterparts. Here, we provide a systematic review and meta-analysis of the SARS-CoV-2 iAg tests’ clinical accuracy.
Gesehen am 25.10.2024